The impacts of development of Pela Village as a tourist village in Kutai Kartanegara, East Kalimantan - I Wayan Lanang Nala; Novita Indriani; I Made Darma Oka (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This study aims to describe the impacts of development of Pela Village as a tourist village in Kutai Kartanegara, East Kalimantan. Pella village has very unique tourism potential to be developed. For the sustainability of tourism development in the tourist village of Pela, it is important to pay attention to the impacts of devel-opment of a tourism village. The data were collected by observation, interviews, and literature study. Inform-ants are taken from community leaders who understand the impacts of tourism development in the village using snowball sampling techniques. Data were analyzed by descriptive qualitative. The results showed that the development of Pela Village as a tourism village able to provide positive impacts for people's lives, both in terms of economic (as lodging business, tour operators, open food stalls); social (effective interactions occur between members of the community): cultural (keeping traditional fishing gear, Kuntau art, and the development of Jepen Dance); environmental (cleaning the village environment), and political dimensions (prioritized local communities as labor). The positive impacts is able to increase the enthusiasm of the local community in supporting the development of tourist villages. It is hoped that stakeholders will play an active role in supporting the development of Pela Tourist Village in the form of guidance, counseling, management, and promotion.